DESIGNING AN INSTITUTIONAL MODEL FOR THE SUNFLOWER AGRO- INDUSTRY SUPPLY CHAIN - Nunung Nurhasanah; Mudrikah, Isna Ibnah (Department of Agroindustrial Technology, Bogor Agricultural University, 2025)
This research aimed to design an institutional model and information system to improve the sustainability of the sunflower agro-industry supply chain in Indonesia. The sunflower agro-industry has great potential, but it is hampered by the lack of an optimal institutional structure. This causes the competitiveness and sustainability of the sunflower agro-industry supply chain to be low. Focusing on the sunflower agro-industry in Bandung Regency and its surroundings, this research used a systems approach to analyze the situational conditions and needs of the sunflower agro-industry. Then, the institutional model was designed using the Interpretive Structural Modeling (ISM) method. Furthermore, the institutional information system model was designed to support institutional operations using the design system approach. The analysis and design of this information system was limited to the design of the graphical user interface, not to the design of the database. The research results show that the situational condition of the sunflower agro-industry was not yet optimal and requires an institutional design that can improve the sustainability and competitiveness of the agro-industry supply chain. Based on the result using ISM, a proposed institutional model was designed. In addition, a design model for a supporting information system was also designed that would support operations in the institutional program. This research is expected to provide contributions to companies with output given in the form of a proposed institutional model design and the basis for creating an institutional information support system. Research can be continued and developed in more depth and can be implemented optimally. Keywords : institutional model, information system, sunflower agro-industry, sustainability, supply chain